Dragon in the air transformation of China's aviation industry and air force - Nigam, Vishal author (K.W. Publishers Pvt. Ltd. in association with Centre for Air Power Studies, 2013)
Dragon in the Air: Transformation of China's Aviation Industry and Air Force is a comprehensive and multidimensional study of the air force and the emerging aviation industry in PRC. The author has made a bold effort to trace the changing character of Chinese Air Force from the time of nationalists and perspicuously hunted down the history by dividing PLAAF into three distinct periods. The first stage from 1949-1979 has been characterized by the early blues of PLAAF under Mao's leadership. Deng then had an overbearing influence in the second stage from 1979-1993, also instrumental in initiating the process of transformation from an ancillary of PLA into an independent arm. The third stage was however the defining moment which witnessed the start of modernisation of PLAAF under the leadership of Jiang Zemin. The author has very lucidly tried to explain the strong link between modernisation of PLAAF and the emergence of China's aviation industry and therefore divided the book in two parts. While the first part of the book maintains focus on the air force and the process of modernisation; the second part dwells with the evolution of the aviation industry and the changes in the organisation structure. He has pointedly highlighted China's increasing defence spending and growing military capabilities resulting in China developing new aerial platforms, ballistic missiles and modern firepower. As a result China is enhancing strategic power projection by building capabilities to carry out air strikes, reconnaissance and early warning and air and missile defence to put together a potent military force by the middle of this century.